Expression profile of immunophenotypic marker molecules on B-lymphocytes in patients with chronic lymphocytic leukemia at the stages of immunochemotherapy - O. N. Selyutina; N. K. Guskova; I. B. Lysenko; M. A. Konovalchik (Южно-Российский онкологический журнал)
Purpose of the study. To study the expression of immunophenotypic marker molecules on B-lymphocytes of patients with chronic lymphocytic leukemia at the stages of immunochemotherapy while monitoring minimal residual disease.Patients and methods. 20 patients with CLL were examined, who in the period 2019–2022 underwent 6 courses of immunochemotherapy (ICT) in the RB/FCR mode at the National Medical Research Centre for Oncology, Rostov-on-Don. Before, after 3, 6 courses of ICT, bone marrow immunophenotyping was performed by flow cytometry. The data is evaluated in Statistica 13.0.Results. Before treatment, 3 groups of patients were identified depending on the expression of prognostic markers (CD38, ZAP‑70, CD11c, CD25, FMC7). I (2 people) – without expression of CD38, ZAP‑70, CD11c, CD25, FMC7 on tumor B-lymphocytes. II (14 people) – with variable expression of CD25, CD38 (0.4–47.6 % and 0.0–57.5 %, respectively), lack of expression of ZAP‑70, CD11c, FMC7. III (4 people)– with high expression of CD38 (57.5–69.2 %), ZAP‑70 (36.6–48.3 %), CD11c (20.0–96.5 %), CD25 (64.9–92.7 %), FMC7 (13.6–88.6 %). After the 3rd course of ICT, the minimum residual disease (MRD): 0 % in group I, 0.48 ±  0.13 % in group II, 33.5 ± 7.84 % in group III. After the 6th course of ICT MRD: 0 % in group I, 0.42 ± 0.09 % in group II, 33.2 ± 8.07 % in group III. The expression of immunophenotypic markers in groups II and III remained unchanged after 3, 6 courses of ICT. According to the criteria for assessing the response to therapy (IWCLL, 2018), patients of groups I, II after the 6th course of ICT have complete remission, 3 patients of group III have partial remission, 1 patient has stabilization of the process. Preliminary data have been obtained indicating that the absence or increased expression of CD38, CD25, ZAP‑70, CD11c, FMC7 on B-lymphocytes of CLL patients before treatment may predetermine the hematological response to therapy according to RB/FCR regimens.Conclusion. Initially, increased expression of all prognostic antigens simultaneously: CD38, CD25, ZAP‑70, CD11c, FMC7 on the tumor population of B-lymphocytes in patients with CLL is associated with an unsatisfactory response to treatment, which seems promising from the point of view of studying the effect of the analyzed marker molecules on achieving a hematological response at the stages of immunochemotherapy.